Study of jets produced in association with a W boson in pp collisions at √s=7 TeV with the ATLAS detector - Anduaga, Xabier Sebastián (2012)
We report a study of final states containing a boson and hadronic jets, produced in proton-proton collisions at a center-of-mass energy of 7 TeV. The data were collected with the ATLAS detector at the CERN LHC and comprise the full 2010 data sample of 36 pb⁻¹. . Cross sections are determined using both the electron and muon decay modes of the boson and are presented as a function of inclusive jet multiplicity, jet, for up to five jets. At each multiplicity, cross sections are presented as a function of jet transverse momentum, the scalar sum of the transverse momenta of the charged lepton, missing transverse momentum, and all jets, the invariant mass spectra of jets, and the rapidity distributions of various combinations of leptons and final-state jets. The results, corrected for all detector effects and for all backgrounds such as diboson and top quark pair production, are compared with particle-level predictions from perturbative QCD. Leading-order multiparton event generators, normalized to the next-to-next-to-leading-order total cross section for inclusive -boson production, describe the data reasonably well for all measured inclusive jet multiplicities. Next-to-leading-order calculations from MCFM, studied here for jet ≤2, and BlackHat-Sherpa, studied here for jet ≤4, are found to be mostly in good agreement with the data.